2018
DOI: 10.3389/fneur.2018.00274
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Saccades in Cerebellar Ataxias Reveal a Contribution of the Cerebellum in Executive Functions

Abstract: ObjectiveIncreasing evidence suggests a cerebellar contribution to modulate cognitive aspects of motor behavior and executive functions. Supporting findings come from studies on patients with neurodegenerative diseases, in which however, given the extent of the disease, the specific role of the cerebellum, could not be clearly isolated. Anti-saccades are considered a sensitive tool to test executive functions. The anti-saccade underlying neural network, consisting of different cortical areas and their downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 92 publications
2
10
0
Order By: Relevance
“…This suggests that the observed activity was not merely an efference copy of the motor command but reflects the preparatory or planning phase of the voluntary movement in which the PC firing is determined by the cue. This is in line with the recent findings in patients with spinocerebellar ataxia type 2 and the late onset of cerebellar ataxia, who are presented with deficits in executive functions during an antisaccade test ( Pretegiani et al, 2018 ) and in patients with cerebellar atrophy who show impairments when making goal-oriented movements ( Piu et al, 2019 ). To what extent the SS responses in our study also correlate with the presence or absence of reward at the end of the trials remains to be seen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that the observed activity was not merely an efference copy of the motor command but reflects the preparatory or planning phase of the voluntary movement in which the PC firing is determined by the cue. This is in line with the recent findings in patients with spinocerebellar ataxia type 2 and the late onset of cerebellar ataxia, who are presented with deficits in executive functions during an antisaccade test ( Pretegiani et al, 2018 ) and in patients with cerebellar atrophy who show impairments when making goal-oriented movements ( Piu et al, 2019 ). To what extent the SS responses in our study also correlate with the presence or absence of reward at the end of the trials remains to be seen.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesize that through the pre-learned associations of parallel fiber and climbing fiber signals, relevant evidence from the stimulus (i.e., dot color in instruction) for the selection of the required action (i.e., pro- or anti-saccade) can be rapidly relayed from the lateral cerebellum to the frontal saccade areas. In cerebellar patients, latencies for antisaccades are prolonged, indicating a less efficient decision-making process in the absence of cerebellar input ( Pretegiani et al, 2018 ; Piu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar relationship was not detected in the FA group. Previously published studies indicated higher antisaccadic error rates in other hereditary and idiopathic cerebellar disorders, including ataxia with oculomotor apraxia type 1, 2, ataxia telangiectasia, SCA1, 2, 3 and late onset cerebellar ataxia (LOCA) [ 28 , 33 35 ]. Additionally, Pretegiani et al revealed that SCA2 and LOCA patients showed equally poor antisaccade performance irrespective of cortical involvement [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies indicated higher antisaccadic error rates in other hereditary and idiopathic cerebellar disorders, including ataxia with oculomotor apraxia type 1, 2, ataxia telangiectasia, SCA1, 2, 3 and late onset cerebellar ataxia (LOCA) [28,[33][34][35]. Additionally, Pretegiani et al revealed that SCA2 and LOCA patients showed equally poor antisaccade performance irrespective of cortical involvement [33]. Additionally, a thorough investigation of a SCA2 patient cohort confirmed that impaired antisaccade efficacy was associated with executive test deficits, including Stroop interference task and verbal fluency test [34].…”
Section: Discussionmentioning
confidence: 99%
“…Saccadic slowing was present even in the early stage of SCA2, can insidiously progress, eventually leading to ophthalmoplegia in late stage (Velázquez-Pérez et al, 2009;Stephen and Schmahmann, 2019). It has been reported a saccadic pursuits, nystagmus, saccadic hypometria, prolonged latency and increased rate of directional errors of anti-saccades in SCA2 (Rodríguez-Labrada et al, 2011;Pretegiani et al, 2018). SCA2 patients may not have typical gaze-evoked nystagmus of cerebellar disease in relation to impaired ability to produce saccadic corrective phases (Geiner et al, 2008).…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%